English Kraftivisme Rajut Kejut: Membangkitkan eksistensi diri di tengah pandemi Covid-19 melalui "Sesaji Nusantara" - Sari Wulandari; Guntur -; M. Dwi Marianto (Mudra Jurnal Seni Budaya, 2022)
The Covid-19 pandemic has forced people to minimize their activities and choose essential things to do. Apart from maintaining personal and environmental hygiene, mental health is the priority. The RajutKejut Community is a group of female crocheters who yarn bombs with crochet works. RajutKejut received an invitation from the Jakarta Biennale 2021 to exhibit their work in a public space. Their work “Sesaji Nusantara”, presented a crochet installation in the form of flowers and crops arrangements, as an offering to God. Through crocheting in a quarantine atmosphere, a space for reflection and contemplation is formed. This is essential to consider that besides preserving quality intake, the body's immunity can also be increased by maintaining mental health and happiness. As a research question, how RajutKejut community through activity body by making communal crafts can create an understanding of themselves and their environment, which is an understanding that leads to the formation of mental health amid the Covid-19 pandemic. This study uses the phenomenological perception by Maurice Merleau-Ponty as an analysis method which is bodily experiences could help people to comprehend their world, particularly in the current pandemic situation. At the end of the discussion, this research shows that the pandemic conditions encourage people to look back at the past, realize their existence in present, and project themselves to plan their next steps. This can be realized by carrying out bodily activities consciously, which brings humans back to retrace their existence in the world as humans who have bodies that can 'make' to fulfill their needs, using their bodies, therefore that awareness of self and self-existence is awakened.